STRATEGI PEMBELAJARAN DARING DENGAN MENGGUNAKAN MEDIA ONLINE SELAMA PANDEMI COVID 19 DI STIKES RS ANWAR MEDIKA - Ahmad suwito Suwito (Basastra, 2021)
The outbreak of the covid-19 virus has changed the life of society, especially in Indonesia. The education sector in Indonesia has also experienced the impact of the covid 19 virus, causing all schools and campuses to use online learning, the government has decided to work at home. As a lecturer, you have to do online learning with a variety of learning methods. The research emphasizes the learning effect of Stikes RS Anwar Medika.Online learning for students who use the internet network in various ways online learning methods with various online media. Overcoming in online learning to students in the form of signals. Learning strategy as a plan that contains a series of activities that are arranged neatly and systematically. This type of research uses a descriptive qualitative approach because this study aims to describe a natural phenomenon. The place of research was carried out at Stikes Rs anwar medika for students in 2020. Data collection techniques were carried out with various methods, namely observation methods, interview methods, documentation methods for data analysis in qualitative research directed to answer the formulation of the problem.The results of the research are 1) Online learning strategies that are applied during the COVID-19 pandemic. 2) there are supporting and inhibiting factors for online learning activities during the covid-19 pandemic, 3) the media used are zoom, whatsapp and Google Classroom. 4) the results of student achievements in online learning during the covid-19 period.